1998
DOI: 10.1002/(sici)1096-9136(1998120)15:12<1039::aid-dia710>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

No deterioration in insulin sensitivity, but impairment of both pancreatic β-cell function and glucose sensitivity, in Japanese women with former gestational diabetes mellitus

Abstract: To identify the primary pathogenic factors involved in the development of Type 2 diabetes mellitus (DM), we studied Japanese women with former gestational diabetes mellitus (GDM) who are at risk for the later development of Type 2 DM. We used the minimal model analysis derived from frequently sampled intravenous glucose tolerance test (FSIGT). The subjects consisted of eight non-obese women with a history of GDM and eight non-obese normal women as control subjects. The 75 g oral glucose tolerance test (75 g OG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…Our results are in agreement with those of some previous studies, 7,8,32 where AIR was not different in a group of normotolerant fGDM women compared to control subjects of similar age and BMI. In other studies, 4,12 AIR was lower in normotolerant fGDM.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our results are in agreement with those of some previous studies, 7,8,32 where AIR was not different in a group of normotolerant fGDM women compared to control subjects of similar age and BMI. In other studies, 4,12 AIR was lower in normotolerant fGDM.…”
Section: Discussionmentioning
confidence: 52%
“…Even greater differences have been observed for betacell function. Insulin secretion has been found impaired, [1][2][3][4][5][6]8,12 normal, 7,9,11,13 and even increased. 10 A possible reason for these different findings is that several investigations included subjects with different glucose tolerance studied as a group.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin sensitivity and secretion in fGDM have been assessed in numerous studies [24–32], which have shown the presence of insulin resistance and impaired β‐cell function. Many of these studies, however, have focused on insulin sensitivity rather than β‐cell function, and are not directly comparable with our work, as the typical fGDM population includes obese, insulin‐resistant and possibly glucose intolerant subjects [24–27].…”
Section: Discussionmentioning
confidence: 99%
“…The view, however, that multiple insulin injections are desirable for type 2 diabetes is not common in Western countries (26,27), because among other reasons, it is feared that exogenous insulin will promote weight gain. In Japanese, however, weight gain is less of a concern, and diminished insulin secretion appears to be the pivotal event, making this population particularly vulnerable to the deleterious effects of insulin resistance (28)(29)(30). In other words, Japanese subjects may be more prone to develop 'insulinopenia' with less provocation than Westerners.…”
Section: Discussionmentioning
confidence: 89%